The Gospel of Thomas and Christian origins : essays on the Fifth Gospel - Patterson, Stephen J., 1957- (Nag Hammadi and Manichaean studies, 2013)
Ten seminal essays on the Gospel of Thomas from a scholar whose work has been at the center of the Thomas debate for more than two decades.